Adaptive backsteping control of electrical transmission drives with elastic and unknown backlash nonlinearity. - Đông, Huỳnh Văn; Kiên, Trần Xuân; Định, Nguyễn Công (Journal of Computer Science and Cybernetics, 2012)
See full text.